2002
DOI: 10.1046/j.1445-2197.2002.t01-1-02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand‐assisted laparoscopic adrenalectomy: An alternative minimal invasive surgical technique for the adrenal gland

Abstract: Hand-assisted laparoscopic adrenalectomy is an easily performed technique, which can be completed within a short operative time span and which has the advantage of providing intraoperative tactile localization for the adrenal gland. It may be particularly applicable for large adrenal tumours, yet only involves the performance of a small abdominal incision. Postoperative recovery is comparable with that reported for the laparoscopic-only technique. Hand-assisted adrenalectomy is a new technique which has great … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…The relative contraindications to laparoscopic adrenalectomy include tumors larger than 10-12 cm (although some authors have reported successful laparoscopic resection of tumors measuring up to 15 cm), significant peritumoral adhesions, invasion of adjacent structures, lymphadenopathy, and evidence of metastatic disease [1,2]. The introduction of the hand-assist device has given surgeons an alternative approach for the resection of selected tumors that might otherwise require open adrenalectomy [7]. The hand-assist device allows the surgeon to palpate the adrenal tumor and resection bed directly, and facilitates removal of large tumors, but does not require as extensive an incision as open adrenalectomy.…”
Section: Laparoscopic Adrenalectomymentioning
confidence: 99%
“…The relative contraindications to laparoscopic adrenalectomy include tumors larger than 10-12 cm (although some authors have reported successful laparoscopic resection of tumors measuring up to 15 cm), significant peritumoral adhesions, invasion of adjacent structures, lymphadenopathy, and evidence of metastatic disease [1,2]. The introduction of the hand-assist device has given surgeons an alternative approach for the resection of selected tumors that might otherwise require open adrenalectomy [7]. The hand-assist device allows the surgeon to palpate the adrenal tumor and resection bed directly, and facilitates removal of large tumors, but does not require as extensive an incision as open adrenalectomy.…”
Section: Laparoscopic Adrenalectomymentioning
confidence: 99%
“…Bennett and Ray 27 were the first to report the successful use of transperitoneal hand-assisted laparoscopic adrenalectomy in three cases of small adrenal tumors (1-3.5 cm in diameter). They concluded that the handassisted approach is technically feasible and reported comparable outcomes with those seen in the laparoscopiconly technique.…”
Section: Discussionmentioning
confidence: 99%
“…However, HALS is not commonly used for endoscopic adrenalectomy, especially for retroperitoneal approaches. Bennett and Ray [2] first reported successful transperitoneal HALS in endoscopic adrenalectomy. They concluded that transperitoneal HALS is a feasible and less invasive alternative procedure for larger tumors and potentially malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Hand-assisted laparoscopic surgery (HALS) is an established alternative procedure in various types of laparoscopic surgery [9,10,14,15,21], including transperitoneal endoscopic adrenalectomy [2,8,16,17]. However, HALS is rarely performed in retroperitoneal endoscopic adrenalectomies because of the narrow working area.…”
mentioning
confidence: 99%